Breast cancer mortality in participants of the Norwegian Breast Cancer Screening Program. Issue 17 (29th May 2013) - Hofvind, Solveig; Ursin, Giske; Tretli, Steinar; Sebuødegård, Sofie; Møller, Bjørn
<x xml:space="preserve">Abstract</x> BACKGROUND The Norwegian Breast Cancer Screening Program started in 1996. To the authors' knowledge, this is the first report using individual‐based data on invitation and participation to analyze breast cancer mortality among screened and nonscreened women in the program. METHODS Information on dates of invitation, attendance, breast cancer diagnosis, emigration, death, and cause of death was linked by using unique 11‐digit personal identification numbers assigned all inhabitants of Norway at birth or immigration. In total, 699, 628 women ages 50 to 69 years without prior a diagnosis of breast cancer were invited to the program from 1996 to 2009 and were followed for breast cancer through 2009 and death through 2010. Incidence‐based breast cancer mortality rate ratios (MRRs) were compared between the screened and nonscreened cohorts using a Poisson regression model. The MRRs were adjusted for calendar period, attained age, years since inclusion in the cohorts, and self‐selection bias. RESULTS The crude breast cancer mortality rate was 20.7 per 100, 000 women‐years for the screened cohort compared with 39.7 per 100, 000 women‐years for the nonscreened cohort, resulting in an MRR of 0.52 (95% confidence interval, 0.47‐0.59). The mortality reduction associated with attendance in the program was 43% (MRR, 0.57; 95% confidence interval, 0.51‐0.64) after adjusting for calendar period, attained age, years after inclusion in the cohort, and self‐selection bias. CONCLUSIONS After 15 years of follow‐up, a 43% reduction in mortality was observed among women who attended the national mammographic screening program in Norway. Cancer 2013;119:3106–3112. © 2013 American Cancer Society.